2011
DOI: 10.1371/journal.pone.0016209
|View full text |Cite
|
Sign up to set email alerts
|

Lkb1 and Pten Synergise to Suppress mTOR-Mediated Tumorigenesis and Epithelial-Mesenchymal Transition in the Mouse Bladder

Abstract: The AKT/PI3K/mTOR pathway is frequently altered in a range of human tumours, including bladder cancer. Here we report the phenotype of mice characterised by deletion of two key players in mTOR regulation, Pten and Lkb1, in a range of tissues including the mouse urothelium. Despite widespread recombination within the range of epithelial tissues, the primary phenotype we observe is the rapid onset of bladder tumorigenesis, with median onset of approximately 100 days. Single deletion of either Pten or Lkb1 had no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 58 publications
(102 reference statements)
4
50
0
Order By: Relevance
“…Our findings are supported by the lack of clonal growth of polyp epithelium addressed in this study, and in PJS polyps previously analyzed with the HUMARA assay (3). Also, the observation that deletion of Lkb1 in GI epithelial cells does not result in a significant decrease in mouse lifespan (41) and that Lkb1 loss from smooth muscle cells using Tagln-Cre ERT2 led to development of PJS-type polyps, strongly support our view that stroma is the critical site of tumor suppression by Lkb1 (6). Interestingly, the observations here with Fsp1-Cre and earlier with Tagln-Cre ERT2 (6) suggest that homozygous deletion of Lkb1 in stroma enhances tumorigenicity while heterozygous deletion is sufficient for polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are supported by the lack of clonal growth of polyp epithelium addressed in this study, and in PJS polyps previously analyzed with the HUMARA assay (3). Also, the observation that deletion of Lkb1 in GI epithelial cells does not result in a significant decrease in mouse lifespan (41) and that Lkb1 loss from smooth muscle cells using Tagln-Cre ERT2 led to development of PJS-type polyps, strongly support our view that stroma is the critical site of tumor suppression by Lkb1 (6). Interestingly, the observations here with Fsp1-Cre and earlier with Tagln-Cre ERT2 (6) suggest that homozygous deletion of Lkb1 in stroma enhances tumorigenicity while heterozygous deletion is sufficient for polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is important to elucidate the molecular targets that can prevent cancer metastasis. Although tumor suppressor genes are thought to work in concert to inhibit cancer (2,3), the molecular mechanisms in this process are not clearly understood. In 2000, we identified a novel protein, Nischarin, as an ␣5 binding protein (4).…”
mentioning
confidence: 99%
“…Nischarin inhibits Rac-induced migration and invasion in breast and colon epithelial cells (6). p21-activated kinase (PAK), 2 a downstream effector of Rac and Cdc42, is linked to cancer. High expression of PAK is detected in several breast tumor types, and activation of PAK leads to increased DNA synthesis, cell proliferation, anchorage-independent growth (7), and tumor growth (8).…”
mentioning
confidence: 99%
“…In vitro studies suggested that PTEN is capable of inhibiting cell proliferation and promoting apoptosis via inhibition of the activity of the PI3K-Akt-mTOR pathway (41). The combined deletion of PTEN and Lkb1 in the mouse bladder significantly activated the mTOR pathway and increased bladder epithelial cell proliferation and tumorigenesis (42). When we compared the mTOR -/PTEN + and mTOR + /PTEN -groups, the differences between them were statistically significant with regard to invasive depth, histological type, lymph node metastasis and pathological stage.…”
Section: Discussionmentioning
confidence: 99%